SCHENGEN receptor module drives localized ROS production and lignification in plant roots. (18th March 2020) - Fujita, Satoshi; De Bellis, Damien; Edel, Kai H; Köster, Philipp; Andersen, Tonni Grube; Schmid‐Siegert, Emanuel; Dénervaud Tendon, Valérie; Pfister, Alexandre; Marhavý, Peter; Ursache, Robertas; Doblas, Verónica G; Barberon, Marie; et al.
Abstract: Production of reactive oxygen species (ROS) by NADPH oxidases (NOXs) impacts many processes in animals and plants, and many plant receptor pathways involve rapid, NOX‐dependent increases of ROS. Yet, their general reactivity has made it challenging to pinpoint the precise role and immediate molecular action of ROS. A well‐understood ROS action in plants is to provide the co‐substrate for lignin peroxidases in the cell wall. Lignin can be deposited with exquisite spatial control, but the underlying mechanisms have remained elusive. Here, we establish a kinase signaling relay that exerts direct, spatial control over ROS production and lignification within the cell wall. We show that polar localization of a single kinase component is crucial for pathway function. Our data indicate that an intersection of more broadly localized components allows for micrometer‐scale precision of lignification and that this system is triggered through initiation of ROS production as a critical peroxidase co‐substrate. Synopsis: In plants, establishment of the Casparian strip diffusion barrier in the root endodermis is achieved by spatially precise deposition of lignin. Here, asymmetrically localized SCHENGEN1 (SGN1) kinase is shown to regulate Casparian strip formation via local induction of ROS‐dependent lignification. Polar localization of SGN1, a cytoplasmic kinase anchored to the plasma membrane, determines localized lignin accumulation in the endodermis. SGN1 transduces activation of the SGN3 receptor by CIF2 secreted peptide. SGN1 locally activates ROS production at the Casparian strip via direct phosphorylation of NADPH oxidases. CIF2‐induced transcriptional changes regulate Casparian strip scaffold establishment and compensatory repair upon barrier defects. Abstract : Polarized activation of SGN1 kinase regulates Casparian strip formation in the root via direct phosphorylation of NADPH oxidases.